Penerapan Location Based Service Pada Absensi Karyawan Berbasis Android Dengan Metode OOAD - Annisa Saraswati; Wiyanto Wiyanto; Edora Edora (Prosiding Sains dan Teknologi, 2022)
One of the technological developments that can be applied within the company is employee attendance activities, and along with the growth of current technology, smartphones are used as a tool to support human activities. This study aims to implement an employee attendance system automation using an Android- based location based service. This application allows employees to more easily take attendance and apply for permission to be absent from work. This application was developed using the OOAD (object oriented analysis and design) method designed using UML (unified modeling language) and a Java-based programming language. The process of testing this application uses black box testing. The research was conducted by collecting data through observation and interviews with related parties at PT. Higashifuji Indonesia. Keywords: Attendance, Android, Location Based Service, OOAD